2022
DOI: 10.3325/cmj.2022.63.117
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic distinction of the Croatian population from the European average

Abstract: Aim To compare the Croatian and European population in terms of allele frequencies of clinically relevant polymorphisms in drug absorption, distribution, metabolism, and excretion (ADME) genes. Methods In 429 Croatian participants, we genotyped 27 loci in 20 ADME genes. The obtained frequencies were merged with the published frequencies for the Croatian population by sample size weighting. The study sample obtained in this way was compared with the average data for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Considering the combined observed frequencies of CYP2C9, CYP2C cluster, CYP4F2, and VKORC1 phenotype combinations in our population, the results point to a muchneeded precaution when prescribing warfarin due to a highly possible gene-drug interaction occurrence altering the patient's response to warfarin. This has been stressed by previous research from Croatian authors and is now further established by adding the observed frequencies of the CYP2C cluster and CYP4F2 gene [21,30]. It is also worth noting that ethnic differences were previously observed for CYP2C9, CYP4F2, and VKORC1, suggesting it may be beneficial to add CYP4F2 testing to algorithms for genotype-based warfarin dosing [31].…”
Section: Warfarin and Coagulation Factor Considerationsmentioning
confidence: 73%
See 1 more Smart Citation
“…Considering the combined observed frequencies of CYP2C9, CYP2C cluster, CYP4F2, and VKORC1 phenotype combinations in our population, the results point to a muchneeded precaution when prescribing warfarin due to a highly possible gene-drug interaction occurrence altering the patient's response to warfarin. This has been stressed by previous research from Croatian authors and is now further established by adding the observed frequencies of the CYP2C cluster and CYP4F2 gene [21,30]. It is also worth noting that ethnic differences were previously observed for CYP2C9, CYP4F2, and VKORC1, suggesting it may be beneficial to add CYP4F2 testing to algorithms for genotype-based warfarin dosing [31].…”
Section: Warfarin and Coagulation Factor Considerationsmentioning
confidence: 73%
“…It is well established that, when present, genotype information should be considered for therapy guidance [18][19][20]. However, a recent study observed a marked difference in allelic frequencies for CYP2B6*4 (24.3% vs. 9.3% in Europe), VKORC1*2 (40.1% vs. 34.9% in Europe), and CYP2C9*2 (14.7% vs. 12.3% in Europe) [21]. In the present study, this was not the case for CYP2B6*4, which was reported at 2.4%.…”
Section: Discussionmentioning
confidence: 99%
“…More than 60 allele variations of the highly polymorphic CYP2C9 gene have been identified other than the normal "wild-type" gene allele (CYP2C9*1), each of them labeled by a star (*) allele nomenclature [3,4] . Besides the normal gene allele, CYP2C9*2 (3608C>T; p.Arg144Cys; rs1799853) and CYP2C9*3 (42614A>C; p.Ile359Leu; rs1057910) are the most commonly reported polymorphisms associated with a lack of enzyme activity among Europeans, with an allele frequency of 12.28% and 6.67%, respectively [3,5]. CYP2C9*2 and *3 polymorphisms are defined by a single nucleotide substitution 3608C>T in exon 3 and 42614A>C in exon 7, respectively resulting in decreased enzyme activity in CYP2C9*2 and no enzyme activity in CYP2C9*3 [4,6] .…”
Section: Introductionmentioning
confidence: 99%